Pedagogia específica de orientação de estágio: uma investigação narrativa - Stahl, Luana Rosalie (2017)
This doctoral thesis was developed in the Research Line 1 - Training, Knowledge and Professional Development of the Post-Graduation Program in Education at Federal University of Santa Maria (UFSM). It is related to studies in the field of University Pedagogy and Teacher Training, carried out by the CNPq research group Formation Trajectory - GTFORMA. The general objective of this thesis was to understand how the specific pedagogy of supervised teacher internship is constituted. The methodological approach was the narrative research, guided by the paradigmatic understanding of the phenomena studied. The instruments used in the research were official documents and narrative interview to transform oral histories into materialized narratives. Teacher educators of supervised teacher internship programs from 14 undergraduate teaching departments of UFSM collaborated in this study. Lee Shulman's professional knowledge and teaching background, as well as the pedagogical reasoning process and the pedagogical content knowledge are theoretical elements that support the discussions and reflections on teacher education. The narratives were submitted to narratological understanding and interpretation. This procedure involved the thematization process, in which different thematic elements constituted three thematic dimensions called: narrative appropriation, teaching trajectories and specific modes of action. They configure a specific mode of teaching performance which was characterized as Specific Pedagogy. The fundamentally narrative feature was recognized, which enables the advisor, through the narrative of the other, to be aware of a different educational space from the one in which he / she works. It was evidenced that the teaching trajectories of these advisors influence teacher conceptions which implicate in how they conceive and carry out the activity of internship supervision. The advisors’ specific modes of action are shaped by the identification of the little or no process of pedagogical reasoning throughout the courses which enable the future teacher to elaborate the pedagogical content knowledge. Thus, the pedagogical content knowledge is implied in the activity of teacher internship supervision, since it involves the combination of knowledge from the specific area and pedagogical knowledge, considering the context in which the internship activity occurs. Dimensions attribute characteristics to the teacher educators’ specific mode of action and shape the pedagogical practices developed by them in the initial training of future teachers. This study does not exhaust the elements which constitute the specific pedagogy. However, it revealed indicators that allowed to assign to the higher education teaching in the disciplines of teacher internship attention by the University Pedagogy as field of study.